Combined effect of different casing and liquid smoked concentration on the shelf - life of sausages produced from fish (Capoeta umbla) - Ozpolat, Emine; Patir, Bahri (Agricultural Research Communication Centre, 2017)
The effect of different casings and liquid smoking solution on the shelf life of new types of sausage from fish (Capoeta umbla) meat was investigated. For preparation of new sausages two casings were used viz. natural casing (N) and synthetic casing (S). The sausages were prepared by adding liquid smoke at 0.1% and 0.5% concentrations. Nutrient compositions of produced sausages were determined on the first day. Microbial, chemical and sensory changes were analyzed throughout the storage time. Results highlighted that fish meat was suitable to produce sausage. Both types of casing exerted similar nutrient composition, microbiological and chemical properties. In general, the highest sensory scores were recorded for the natural casing and 0.1% liquid smoke added sausage.
Keywords: Fish sausage; Liquid smoke; Natural casing; Shelf-life; Synthetic casing